Wideband Tympanometry - Biswas, Anirban; Dutta, Nilotpal (Annals of Otology and Neurotology, 2018)
Traditional tympanometry done with 226 Hz probe tone frequency has some inherent defects and limitations due to which it does not give a very true picture of the middle ear status, and tympanometric findings are often very deceptive. It is not uncommon for otologists to find that on opening the middle ear, the pathology in the middle ear is very different from what they had expected from tympanometric findings. This is because the 226 or 220 Hz, that is used for the traditional single tone tympanometry is based on physical convenience, i.e., practicalities in carrying out the test rather than on test performance, i.e., the diagnostic efficacy of the test. The 226 Hz tympanometry is a poor predictor of middle ear effusions in babies and will be wrong in approximately 50% of cases and diagnosis of ossicular chain discontinuity by type A tympanogram is correct in only about 40% cases, if not lesser. In most cases of otosclerosis, though there is a middle ear stiffness, the tympanometric findings with traditional tympanometry show normal compliance, which is not expected in stiffness of the middle ear. Tympanometry is basically to identify common middle ear pathologies, such as middle ear effusion, ossicular chain discontinuity and otosclerosis. However, if in these very cases the diagnostic efficacy is so poor, then the objective of the test is lost. Traditional tympanometry has a lot of limitations and fallacies. These issues led scientists to sharpen the diagnostic efficacy of tympanometry and the final outcome of the research is wide band tympanometry (WBT). The special advantages of WBT, its difference from traditional single frequency tympanometry, and its clinical utility are presented in this article. Here, we review the concept of WBT, the basic mechanism, and its vast clinical applications. Most of the deficiencies of traditional tympanometry have been overcome by WBT. Not only that, the scope of tympanometry has been further widened by WBT and in addition to diagnosing middle ear pathologies with much more confidence, it can also be used for postoperative monitoring using non-pressurized wideband absorbance.
Keywords: middle ear; traditional tympanometry; wideband tympanometry